Origin of the spin-triplet Andreev reflection at ferromagnet/ s -wave superconductor interface - Feng, Cui Di; Zheng, Zhi Ming; Ji, Yi Qun; Niu, Zhi Ping; Xing, D. Y. (Journal of applied physics, 2008)
To understand the origin of the spin-triplet Andreev reflection which may appear at a ferromagnet ( F ) / s -wave superconductor ( S ) interface, we study tunneling conductance spectra of F / 2 DEG / s -wave S tunnel junctions, with 2DEG the two-dimensional electron gas with Rashba spin-orbit coupling and subject to a magnetic field. It is found that both spin-flip and broken time-reversal symmetry in the 2DEG are conditions necessary to giving rise to the novel Andreev reflection and spin-triplet pairing correlations.